Medico-botanical report on the Chakma community of Bangladesh - Roy, Snigdha; Uddin, Mohammad Zashim; Hassan, Md. Abul; Rahman, M. Matiur (Bangladesh Journal of Plant Taxonomy, 2008)
Not available. DOI: 10.3329/bjpt.v15i1.929 Keywords: Chakma tribe; Ethnobotany; Bangladesh Bangladesh J. Plant Taxon. 15(1): 67-72, 2008 (June)